Bahasa Reformasi: Political Rhetoric in Post-Suharto Indonesia. Volume 6 of Frankfurter Forschungen zu Südostasien by Arndt Graf, Wiesbaden: Harrassowitz Verlag, 2010. (KEMANUSIAAN The Asian Journal of Humanities, 2011)
GRAF, Arndt. 2010. Bahasa Reformasi: Political Rhetoric in Post-Suharto Indonesia. Volume 6 of Frankfurter Forschungen zu Südostasien. Wiesbaden: Harrassowitz Verlag, pp. 1–202. ISBN: 9783447063913